Screening and identification of extracellular lipase-producing thermophilic bacteria from a Malaysian hot spring - Sheikh Abdul Hamid, Nazimah; Zen, B. Hee; Ong, Bee Tein; M. Halifah, Yasin; Saari, Nazamid; Abu Bakar, Fatimah (Kluwer Academic Publishers, 2003)
Seven lipase-producing thermophilic bacteria (ST 1, ST 4, ST 6, ST 7, ST 8, ST 9 and ST 10) were isolated from the Setapak hot spring in Malaysia. The crude extracellular lipases recovered by ultrafiltration of cell-free culture supernatant were reacted in an olive oil mixture and their lipolytic activities were compared. Identification of the bacteria was carried out using the Biolog system and biochemical tests. Strain ST 7 that exhibited the highest lipolytic activity of 4.58 U/ml was identified as belonging to the Bacillus genus. Strain ST 6 with an activity of 3.51 U/ml, was identified as Ralstonia paucula. The lipolytic activities of strains ST 1, ST 4, ST 8, ST 9 and ST 10 were 2.39, 1.84, 2.38, 1.80 and 2.62 U/ml respectively. Strains ST 1, ST 4, and ST 10 were identified as Ralstonia paucula while strains ST 8 and ST 9 were Bacillus spp. Strains ST 7 and ST 9 were tentatively identified as Bacillus thermoglucosidasius, Bacillus stearothermophilus or Bacillus coagulans, whereas strain ST 8 was tentatively identified as Bacillus subtilis.